Working as a Researcher in Spain: Does the PHD duration matter? - Caparrós-Ruiz, Antonio (My University, 2017)
The Lisbon Strategy has enhanced the role of the education and the research as the cornerstones of the economic growth and the job creation in the EU. Therefore, analyzing the transmission channels of the human capital investments to the society is important to inform students and policymakers about the opportunities and benefits related to the acquisition of education. In this context, PhD programs have a relevant role to reach the European research goals. This study contributes to shed empirical evidence about the determinants of the time to the doctorate in Spain and its influence on the probability of working as a researcher. One of the main hypothesis to verify is whether a prolonged time to complete the doctoral studies is a negative signal about the individual’s capacity to develop research skills. If this is really the case, longer time to doctorate would imply less probability of working as a researcher. The methodology applied consist, on the one hand, in estimating a Cox model with shared frailty to analyse the determinants of the time to the doctorate and, on the other hand, a probit model to analyse the probability of being a researcher considering time to the doctorate as an endogenous regressor. Data used come from the 2009 Survey on Human Resources in Science and Technology, provided by the Spanish National Institute of Statistics (INE 2010).
Keywords: Cursos de postgrado; Time to doctorate; PhD program; Researcher